Perspektif Hukum Islam tentang Akad Qardh dalam Pembayaran (Paylater) Jual-beli Online Aplikasi Marketplace Shopee - Muflihatul Isnaeni; Intan Cahnia; Indah Nurazizah; Musyaffa Amin Ash Shabah (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
Paylater in e-commerce creates a contemporary business style not directly, so there is no need to bring in real buying and selling actors and without wearing an original signature. The paylater payment method is a method that can be paid in installments, where buyers can get orders before paying, because paylater is a financial tool from Shopee. This research is to describe the perspective of Islamic law regarding qardh contracts in payments paylater for online buying and selling of the Shopee marketplace application and the benefits for its users. This type of research is directed and focused on discussing library materials, both books, web and journals. Using a qualitative approach which is carried out through online research to look for theories and concepts of Islamic law qardh contract, especially in payments (paylater) on the Shopee marketplace application according to the DSN-MUI Fatwa No.19/DSN-MUI/IV/2001 concerning qardh. Analyzed using the Descriptic-Analytic method to describe the thoughts of these scholars. The results of this study, according to DSN-MUI Fatwa No.19/DSN-MUI/IV/2001 regarding qardh, that in its provisions, qardh customers are required to return the principal amount received at the agreed time. So this is legally permissible because there is a clear agreement.